The incentive effects of long-term contracts on performance - Evidence from a natural experiment in European Football - Michael Gerfin; Eberhard Feess; Gerd Mühlheusser (Verein für Socialpolitik, 2010)
The empirical analysis of the impact of long-term contracts on performance is challenging for two reasons: first, it is difficult to get adequate performance measures and second, potentially negative incentive effects of long-term contracts are countervailed by selection effects when workers with higher abilities get longer contracts. We adopt data from professional sports to disentangle selection and incentive effects. The famous Bosman judgement in European football provides a natural experiment as it has led to an exogenous increase in the contract length of players independently of ability, and can hence be used as an instrumental variable to solve the endogeneity problem associated with the contract length. Using data from the German Bundesliga, we find evidence that long-term labor contracts reduce average performance of professional players. In addition, we find that longer contracts influence the distribution of performance asymmetrically in the sense that they increase the probability of poor performances but do not reduce the probabilities of good performances.
Keywords: J44; C21; J41; 330; contracts; incentive effects; moral hazard; instrumental variables; natural experiment